2003
DOI: 10.2135/cropsci2003.1741
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Comparison of Progeny Derived from 4x‐2x and 4x‐4x Hybridizations of Lotus glaber Mill. and L. corniculatus L

Abstract: ble the chromosome number of 2x diploid Lotus species (2n ϭ 2x ϭ 12 or 14) for germplasm transfer to L.Unreduced gametes (2n gametes) from Lotus glaber Mill. (2n ϭ corniculatus: (i) autotetraploid production by colchi-2x ϭ 12) may aid intercrossing with L. corniculatus L. (2n ϭ 4x ϭ 24) to produce progeny with a greater heterotic advantage than progeny cine-induced chromosome doubling of 2x species, and derived from colchicine-induced {7-acetamido-6,7-dihydro-1,2,3,10-(ii) 2n gametes to create 4x interspecific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…report that sexual polyploids have been much more useful for crop improvement than mitotic polyploids. Beuselinck et al (2003) has shown that 2n gametes from Lotus glaber may aid intercrossing with Lotus corniculatus to produce progeny with a greater heterotic advantage than progeny obtained from the colchicine induced tetraploid (4x) Lotus glaber. In alfalfa, McCoy & Rowe (1986) showed better breeding value of 2n gametes from the diploids than n gametes from chromosome doubled tetraploids.…”
Section: Role Of 2n Gametes In Plant Breedingmentioning
confidence: 99%
“…report that sexual polyploids have been much more useful for crop improvement than mitotic polyploids. Beuselinck et al (2003) has shown that 2n gametes from Lotus glaber may aid intercrossing with Lotus corniculatus to produce progeny with a greater heterotic advantage than progeny obtained from the colchicine induced tetraploid (4x) Lotus glaber. In alfalfa, McCoy & Rowe (1986) showed better breeding value of 2n gametes from the diploids than n gametes from chromosome doubled tetraploids.…”
Section: Role Of 2n Gametes In Plant Breedingmentioning
confidence: 99%
“…On the other hand, tetraploid L. japonicus produced in our study had significantly shorter pods and fewer seeds per pod than the diploid L. japonicus . Beuselinck et al (2003) reported that pollen tube growth of the tetraploid was reduced to 32%, whereas pollen tube germination of the diploid was 90% in L. tenuis . In general, plants with doubled genomes have low fertility (Beuselinck et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome doubling through the application of spindle‐toxins, such as colchicine or oryzalin, is an established technique to create new autopolyploid varieties and overcome ploidy‐based hybridization barriers. Colchicine or oryzalin have been applied to various plant parts including roots (Sebastiampillai and Jones, 1976), apical meristems (Iyer and Randhawa, 1965; Beuselinck et al, 2003), and seedlings (Swenne et al, 1981; Schifino and Moraes Fernandes, 1987) to create novel tetraploid germplasm in various species. Artificial tetraploids produced by chromosome doubling facilitated gene transfer between species and genera (Simioni and Valle, 2009) and the creation of fertile interspecific hybrids between L. corniculatus and L. tenuis Waldst.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to transfer the indehiscent pod trait from distantly related species via interspecific hybridization (Beuselinck et al 2003), diploid bridge species, amphidiploidy, backcrossing to birdsfoot trefoil or somatic hybridization have been promising. Genetic transformation by Agrobacterium tumefaciens has been carried out in Lotus, starting with the diploid L. japonicus (Handberg & Stougaard 1992).…”
Section: Overcoming Of Pod Dehiscencementioning
confidence: 99%